2013
DOI: 10.1371/journal.pone.0057651
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Ameliorates the Decremental Effect of Paraquat on Cardiomyocyte Contractility in Rats

Abstract: BackgroundExposure to pesticides and industrial toxins are implicated in cardiovascular disease. Paraquat (PAR) is a toxic chemical widely used as an herbicide in developing countries and described as a major suicide agent. The hypothesis tested here is that PAR induced myocardial dysfunction may be attributed to altered mechanisms of Ca2+ transport which are in turn possibly linked to oxidative stress. The mechanisms of PAR induced myocardial dysfunction and the impact of antioxidant protection was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This increase in heart rate may be associated with increased metabolic activity, as the sheep were fed after the 0900 h (basal measurements) measurements of physiological parameters. Interestingly, the heart rate was reduced by the antioxidant supplementation irrespective of thermal treatment, which may be explained by the beneficial effects of Vit E on the cardiac autonomic nervous system as has been reported in rats and humans (Behrens et al, 1986;Manzella et al, 2001;Fahim et al, 2013) In general, exposure of sheep to high ambient temperatures results in decline in feed intake along with the increased respiration rate and rectal temperature, compromising the efforts to dissipate heat (Marai et al, 2007). In this study, we found 13% decline in feed intake of CTRL group when exposed to HS.…”
Section: Discussionmentioning
confidence: 72%
“…This increase in heart rate may be associated with increased metabolic activity, as the sheep were fed after the 0900 h (basal measurements) measurements of physiological parameters. Interestingly, the heart rate was reduced by the antioxidant supplementation irrespective of thermal treatment, which may be explained by the beneficial effects of Vit E on the cardiac autonomic nervous system as has been reported in rats and humans (Behrens et al, 1986;Manzella et al, 2001;Fahim et al, 2013) In general, exposure of sheep to high ambient temperatures results in decline in feed intake along with the increased respiration rate and rectal temperature, compromising the efforts to dissipate heat (Marai et al, 2007). In this study, we found 13% decline in feed intake of CTRL group when exposed to HS.…”
Section: Discussionmentioning
confidence: 72%
“…This may also explain beneficial effects of antioxidant (Vit E) feeding during HS other than reducing the OS in sheep. The beneficial effects of Vit E on the cardiac autonomic nervous system have also been reported to reduce heart rate in rats and humans (Behrens et al, 1986;Manzella et al, 2001;Fahim et al, 2013). An increase in the parasympathetic tone of the autonomic nervous system would be consistent with an improvement in GIT function.…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence also revealed compromised cardiac structure and function Jiaxing Wang, Songhe Lu and Qijun Zheng have contributed equally to this work. including cardiac enlargement, contractile dysfunction and bradycardia [10][11][12][13][14]. Up-to-date, several mechanisms have been postulated for paraquat-induced cellular injury including oxidative stress, disturbed mitochondrial oxidative phosphorylation and respiration events [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%